Major amputations in type 2 diabetes between 2001 and 2015 in Spain: regional differences - María del Cristo Rodríguez Pérez; Chiara Chines; Arturo J. Pedrero García; Djeniffer Sousa; Francisco J. Cuevas Fernández; Itahisa Marcelino-Rodríguez; Santiago Domínguez Coello; Antonio Cabrera de León (BMC, 2020)
Abstract Background To analyze the trend of lower extremity major amputations (MA) among patients with type 2 diabetes mellitus (T2DM) in the Regions of Spain from year 2001 until 2015. Methods Descriptive study of 40,392 MA. Data were obtained from the national hospital discharge database in patients with T2DM. The incidence rate was calculated in each Region, in addition to the incidence ratios (IR) between annual incidence and incidence of the year 2001. The length of hospital stay and mortality risks were analyzed using regression models adjusted for sex, age and smoking. Results The major amputations incidence rate per 100,000 person-years was 0.48 in Spain; Canary Islands showed the highest incidence (0.81). The trend was a slight decrease or stability of the incidence in all Regions except in the Canary Islands (IR2015 = 2.0 [CI95% = 1.5, 2.6]) and in Madrid (IR2015 = 0.1 [CI95% = 0.1, 0.2]). Mortality after major amputations was 10% in Spain; Cantabria suffered the highest risk of death [1.7 (CI95% = 1.4; 2.1), p < 0.001] and La Rioja the lowest risk (0.5 [CI95% = 0.2; 0.9]; p = 0.026). The longest hospital stay was registered in the Canary Islands [(CI95% = 11.4;13.3], p < 0.001)], and the shortest in the Valencian Community [(CI95% = − 7.3; − 5.8), p < 0.001)]. Conclusion MA in T2DM followed a growing trend in the Canary Islands, which diverged from the downward trend in Spain. The variability of mortality and hospital stay, suggest to review the clinical management in some Regions. Sudden incidence decrease in Madrid suggests checking the record procedures of hospital discharges.